2011
DOI: 10.1007/s10802-011-9504-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Parent-Reported Attention-Deficit/Hyperactivity Disorder in Children Aged 6–7 years: A National Longitudinal Study

Abstract: This study examined the prenatal, postnatal and demographic predictors of parent-reported attention-deficit/hyperactivity disorder (ADHD) in an Australian population-based sample. Participants were families participating in the Longitudinal Study of Australian Children. There were approximately even numbers of males (51%) and females (49%) in the sample. Predictors of parent-reported ADHD status at Wave 2 (children aged 6-7 years) which were measured at Wave 1 (children aged 4-5 years) included cigarette smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 46 publications
4
35
1
Order By: Relevance
“…Emotional dysregulation was assessed by items such as: "This child . 39,40 We used this case definition in previous studies using LSAC data 40 and found that children with mother-reported ADHD were very similar to those with clinically elevated ADHD symptoms on the SDQ. Attentional regulation was assessed from Wave 2 only (i.e., not during infancy) by items such as: "This child .…”
Section: Methodsmentioning
confidence: 99%
“…Emotional dysregulation was assessed by items such as: "This child . 39,40 We used this case definition in previous studies using LSAC data 40 and found that children with mother-reported ADHD were very similar to those with clinically elevated ADHD symptoms on the SDQ. Attentional regulation was assessed from Wave 2 only (i.e., not during infancy) by items such as: "This child .…”
Section: Methodsmentioning
confidence: 99%
“…In turn, parental psychopathology is thought to increase children’s risk for ADHD and ODD through a combination of genetic liability for psychopathology and environmental risk (Bornovalova, Hicks, Iacono, & McGue, 2010). Maternal depression and anxiety have been consistently associated with child ADHD and ODD in cross-sectional (e.g., Segenreich et al, 2015; Tully, Iacono, & McGue, 2008) and prospective studies (Ashman, Dawson, & Panagiotides, 2008; O’Connor, Heron, Golding, Beveridge, & Glover, 2002; Sciberras, Ukoumunne, & Efron, 2011). Paternal antisocial symptoms are also associated with trajectories of higher levels of hyperactivity-impulsivity and inattention across early childhood (e.g., Galéra et al, 2011) and with ODD in children (e.g., Blazei, Iacono, & McGue, 2008; Frick et al, 1992).…”
Section: Factors That May Account For the Relation Between Parental Amentioning
confidence: 99%
“…Preschool children, whose mothers reported prenatal anxiety (PNA) during early gestation (Loomans et al, 2011), or mid-to-late gestation (O'Connor, Heron, & Glover, 2002;O'Connor, Heron, Golding, & Glover, 2003) have been found to have an increased risk of Attention Deficit Hyperactivity Disorder (ADHD) and Conduct Disorder (CD)/ behaviour problems. However, prenatal maternal depression (PND) (O'Donnell, Glover, Barker, & O'Connor, 2014;Van Batenburg-Eddes et al, 2013) and maternal post-partum depression (PPD) (Carter, Garrity-Rokous, Chazan-Cohen, Little, & Briggs-Gowan, 2001;Kim-Cohen, Moffitt, Taylor, Pawlby, & Caspi, 2005;Sciberras, Ukoumunne, & Efron, 2011) have also been found related to ADHD and behaviour problems in preschool children. Impaired maternal sensitivity, insecure infant attachment, and less optimal mother-child interactions have been found associated with post-partum depressions (PPD), which may negatively impact on children's further cognitive and behavioural development (Stein et al, 2012a;Carter et al, 2001;Shaw & Vondra, 1995).…”
Section: Introductionmentioning
confidence: 99%